LEGAL REVIEW ON THE LEGALITY OF MARRIAGE CONTRACT REVIEWED FROM LAW NUMBER 1 YEAR 1974 AND ISLAMIC LAW IN MEDAN CITY - Nurul Aisyah (NOMOI Law Review, 2021)
In fact marriage is a sacredness intended for a long time until death separates, but in practice often people who perform a temporary marriage called contract marriage. Given the importance of the issue of marriage, the intricacies regarding marriage have been regulated in such a way both in state law, religion and societal norms. Indonesia as a country that upholds religious values and societal norms is certainly very critical in determining the validity of a marriage. It is stated in the Law No. 1 of 1974 and Government Regulation No. 9 of 1975, the implementation of marriage is an important momentum and must be preserved, then in addition to marriage must be carried out in accordance with each religion and belief, marriage should be recorded, as stipulated in Article 2 of Law No. 1 of 1974 paragraph (1). But even though there are rules regarding the law and conditions of marriage both religiously and governmentally, there are still individuals who perform marriages that are not in accordance with these conditions. One form of marriage that is not in accordance with the terms and laws that apply is contract marriage. With the absence and non-legality in marriage contracts that occur in many communities that are limited only by time and that are contrary to the prevailing legal norms.Keywords: Marriage, Marriage Contract, Legal Arrangements, Legality